Calmodulin as a major calcium buffer shaping vesicular release and short-term synaptic plasticity: facilitation through buffer dislocation - Timofeeva, Yulia; Volynski, Kirill (Frontiers in Cellular Neuroscience, 2015)
Action potential-dependent release of synaptic vesicles and short-term synaptic plasticity are dynamically regulated by the endogenous Ca2+ buffers that shape [Ca2+] profiles within a presynaptic bouton. Calmodulin is one of the most abundant presynaptic proteins and it binds Ca2+ faster than any other characterized endogenous neuronal Ca2+ buffer. Direct effects of calmodulin on fast presynaptic Ca2+ dynamics and vesicular release however have not been studied in detail. Using experimentally constrained three-dimensional diffusion modeling of Ca2+ influx–exocytosis coupling at small excitatory synapses we show that, at physiologically relevant concentrations, Ca2+ buffering by calmodulin plays a dominant role in inhibiting vesicular release and in modulating short-term synaptic plasticity. We also propose a novel and potentially powerful mechanism for short-term facilitation based on Ca2+-dependent dynamic dislocation of calmodulin molecules from the plasma membrane within the active zone.